143 Where's the block for primary prevention implantable cardioverter defibrillators?. (22nd September 2015) - Sadarmin, P P; Wong, K C K; Rajappan, K; Bashir, Y; Betts, T R
Abstract : Introduction: The UK has one of the lowest Implantable Cardioverter Defibrillator (ICD) implant rates in the western world and the majority of implants are for secondary prevention. This study was designed to identify the stumbling blocks for potential primary prevention(PP) ICD recipients who might otherwise qualify for an ICD according to current UK NICE guidelines. Methods: A search was performed on the Oxford Radcliffe Hospitals echocardiography and heart failure databases for pts with an Oxfordshire postcode who had documentation of left ventricular ejection fraction (LVEF) recorded in the calendar year 2007. Pts <18 yrs were excluded. The search criteria included LVEF <35%. In addition, the descriptive terms 'severely impaired' or 'poor LVEF' were taken to indicate LVEF <30% and the term 'moderate to severely impaired' was taken as LVEF 30–35%. Medical notes were assessed for age, aetiology of heart disease, time from MI, 12 lead ECG QRS duration, evidence of NSVT, Holter or electophysiological studies (EPS), NYHA status, review by a cardiologist and ICD implanter. Results: Three hundred nine pts with LVEF <35% were identified from a population of 3554 echo assessments and 1104 heart failure patients. The findings are summarised in Abstract 143 figure 1 . 19.5% pts were deemed not suitable for a PP ICD. 6% pts had subsequent improvement in their LVEF to >35%. Wrong documentation was evident in 5.5% pts. Of the 44 (14%) non-IHD (outside of NICE PP guidelines) pts with LVEF <35%, 24/44 (54.5%) had PP ICDs, usually combined with CRT. Missing data constituted 6.4% of our study. 44% pts satisfied the MADIT 2 and NICE criteria for PP ICDs. Thirty eight per cent of those eligible already had an ICD implanted. Fourty three per cent of pts who meet the NICE criteria were not offered PP ICDs. Forty seven per cent of these pts had been reviewed by a General Cardiologist and 40% by a General Physician. Seventy three per cent of potential MADIT 1 pts did not undergo Holter monitoring±electrophysiological studies (EPS) although 57% of them were seen by a General Cardiologist and none were referred for EPS. Conclusions: In the current study of all patients undergoing echocardiography in 2007, half of those with LVEF <35% fulfilled NICE guidelines for PP ICDs. Only 40% had seen a cardiologist and of those only 38% had been offered a PP ICD. Holter screening of potentially eligible pts is not being performed. The barriers to PP ICDs appear to be at the level of the General Physicians and General Cardiologist.